2022
DOI: 10.1038/s41550-022-01798-6
|View full text |Cite
|
Sign up to set email alerts
|

Oblique and rippled heliosphere structures from the Interstellar Boundary Explorer

Abstract: Past analysis has shown that the heliosphere structure can be deduced from correlations between long-scale solar wind pressure evolution and energetic neutral atom emissions. However, this required spatial and temporal averaging that smoothed out small or dynamic features of the heliosphere. In late 2014, the solar wind dynamic pressure increased by roughly 50% over a period of 6 months, causing a time and directional-dependent rise in around 2–6 keV energetic neutral atom fluxes from the heliosphere observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 107 publications
1
21
0
Order By: Relevance
“…An initial comparison was made by Zirnstein et al (2016) Swaczyna et al (2020) found the interstellar neutral hydrogen density extrapolated to the termination shock using New Horizons SWAP observations of interstellar PUI to be 40% higher than previously thought. To "rebalance" the modeled pressure in the heliosphere, the plasma and neutral densities have since been updated from the original values used by the Zirnstein et al (2016) model in order to be consistent with items (i) and (ii) described above (e.g., Zirnstein et al 2022). However, the VLISM magnetic field parameters remain unchanged because they are separately constrained by the IBEX data, and any change to the magnetic field would cause the modeled ribbon to disagree with IBEX observations.…”
Section: Observations and Simulationmentioning
confidence: 99%
“…An initial comparison was made by Zirnstein et al (2016) Swaczyna et al (2020) found the interstellar neutral hydrogen density extrapolated to the termination shock using New Horizons SWAP observations of interstellar PUI to be 40% higher than previously thought. To "rebalance" the modeled pressure in the heliosphere, the plasma and neutral densities have since been updated from the original values used by the Zirnstein et al (2016) model in order to be consistent with items (i) and (ii) described above (e.g., Zirnstein et al 2022). However, the VLISM magnetic field parameters remain unchanged because they are separately constrained by the IBEX data, and any change to the magnetic field would cause the modeled ribbon to disagree with IBEX observations.…”
Section: Observations and Simulationmentioning
confidence: 99%
“…Furthermore, the enhancement near the heliospheric nose, which is visible in the center of the presented maps, shows the importance of the separation because this enhancement overlaps the ribbon region. The recent enhancement in observed ENA fluxes near this enhancement, which follows the increase in the solar wind dynamic pressure (McComas et al 2019;Zirnstein et al 2022), is clearly visible in separated maps from observations in 2017 and later, especially in the higher energy steps.…”
Section: Resultsmentioning
confidence: 82%
“…Based on the separated signals, we confirm that the GDF and ribbon evolve differently over the solar cycle (Section 3). The GDF shows apparent enhancement following the solar wind dynamic pressure increase in late 2014 (McComas et al 2019;Zirnstein et al 2022). The response observed in the ENA flux is delayed, reflecting the distance to the ENA source region.…”
Section: Discussionmentioning
confidence: 99%
“…We argue that this rapid evolution is related to the opening of a PCH observed at the Sun's south pole in late 2014 (see Figure 1). The region with flatter ENA spectra around the V2 direction (around ecliptic longitude 300°-360°) is likely related to an enhanced ENA production in the higher energy channel of IBEX-Hi due to the SW with higher dynamic pressure observed at 1 au (McComas et al 2018b(McComas et al , 2020Zirnstein et al 2022). A large increase in the 1 au SW dynamic pressure observed in late 2014 was reflected in enhanced ENA emissions at higher energy channels of IBEX-Hi (ESA 4-6) beginning in late 2016.…”
Section: Evolution Of the Polar Ena Spectrum Over The Solar Cycle 24mentioning
confidence: 96%
“…A large increase in the 1 au SW dynamic pressure observed in late 2014 was reflected in enhanced ENA emissions at higher energy channels of IBEX-Hi (ESA 4-6) beginning in late 2016. The enhanced ENA emissions were first observed ∼20°below the nose of the heliosphere and then reached the V2 direction in late 2017 (see Figure 4 in Zirnstein et al 2022).…”
Section: Evolution Of the Polar Ena Spectrum Over The Solar Cycle 24mentioning
confidence: 99%